MODELAÇÃO DO MANANCIAL SUBTERRÂNEO DE RIBEIRÃO PRETO. 1- DESCRIÇÃO DO DOMÍNIO - Montenegro, Abelardo Antônio de Assunção; Righetto, Antônio Marozzi; Sinelli, Osmar (Águas Subterrâneas, 1988)
Resumo não disponível.